498 Improving Surgical and Non-Surgical Oncological Outcomes in Patients with Head and Neck Cancer. (12th October 2021) - Atkinson, B; Wilson, J
Abstract: Introduction: Treatment of head and neck cancer is complex and involves a multi-disciplinary approach between surgeons and oncologists. Radiotherapy often leaves patients with debilitating side effects such as mucositis, sialadenitis and dysphagia. Radiation induces double strand breaks (DSBs) in DNA within both normal squamous cells and squamous cell carcinomas (SCCs) that, if left unrepaired, initiates programmed cell death. Like normal squamous cells, SCC's have an effective DNA repair pathway to protect against apoptosis by repairing DSBs through proteins such as FanD2-S331. This study aims to show that mild hyperthermia inhibits FancD2, therefore having the potential to increase the susceptibility of SCCs to radiotherapy and subsequently reducing the side effects. Method: Head and neck cancer cell line UMSCC47 was cultured, then irradiated with 2 Gray before washing with an anti γH2AX antibody, used as a biomarker for DSBs. Fluorescent antibodies against FacD2-S331 were then used to assess the levels present within the nucleus of cells exposed to mild hyperthermia (39 °C) and then compared to untreated cells and cells exposed to radiation only. Results: A γH2AX fluorophore intensity score of 58 following radiation compared to 20 in the control confirmed the presence of DSBs. A FancD2-s331 fluorophore intensity score of 76 was observed in cells exposed radiation. Cells exposed to heat prior to radiation showed a FancD2-s331 fluorophore score of 21. Conclusions: Exposure of SCCs to mild hyperthermia before radiotherapy reduces activation of DNA repair protein FancD2-S2331. A reduction in DNA repair increases the susceptibility of SCCs to radiotherapy and apoptosis.